Optimisation of the performance and structure of soluble ball seat metal sealing rings based on response surface - CHEN Zhen; RAN Qingjie; CHEN Nengpeng; WANG Qiaomu (工程科学与技术)
Horizontal well fracturing technology, as a core tool for efficient development of tight oil and gas reservoirs, is of strategic significance for enhancing the recovery rate of unconventional oil and gas resources. As a key downhole tool of this technology, soluble ball seat, with its advantages of rapid dissolution, full-pass production and process simplification, can significantly improve the operational efficiency and reduce the cost of well completion, and has been widely used in the development of complex reservoirs such as shale gas. However, the metal sealing ring under the actual downhole working conditions is facing multiple extreme environments such as high temperature (201.8 ℃), high pressure (70M Pa) and casing deformation, which can easily lead to the structural fracture failure and sealing failure of the dissolvable ball seat metal sealing ring, resulting in an increase in the leakage rate of the fracturing fluid, and even inducing downhole accidents. Aiming at this problem, this paper proposes a multi-parameter collaborative optimization strategy based on response surface methodology. Through the combination of multi-structure simulation, response surface optimization design and simulation verification, multi-objective optimization, and high-pressure experimental verification, the structural parameters of the metal sealing ring are systematically revealed to have an impact on the safety and sealing performance, and at the same time, a collaborative design path with "low-stress-high-pressure" is constructed, which provides theoretical basis and experimental support for the optimization of the sealing structure under the complex working conditions. At the same time, a "low stress-high pressure" synergistic design path is constructed, which provides theoretical basis and experimental support for the optimization of seal structure under complex working conditions.The study establishes a three-dimensional parameterized model by combining finite element simulation and experimental verification. Based on single-factor analysis, the key parameters are clarified: in the range of 53~55 mm, increasing the radius can improve the contact pressure, and at the same time will lead to an increase in the equivalent force; in the range of 4~5.665 mm in width, although the wider structure can reduce the rate of stress growth, the contact pressure decreases with the increase in width; the increase in the parameters of the grooves (width and depth of the grooves) can improve the contact pressure, and will increase the equivalent force, which may lead to the localization of the sealing structure. The increase of groove parameters (groove width and depth) can enhance the contact pressure, and at the same time, increase the equivalent stress, which may lead to local strength deficiency.Through the sensitivity analysis, the sensitivity coefficients of the radius of the metal seal ring to the equivalent force and contact pressure were found to reach 0.67 and 0.82, which were the dominant variables affecting the sealing performance; the width and depth of the grooves regulated the stress distribution through the geometric compensation mechanism. On this basis, the Box-Behnken design is used to construct a four-factor and three-level experimental scheme, and a second-order response surface agent model is established by 25 sets of simulation data, with the dual optimization objectives of minimizing the equivalent force and maximizing the contact pressure, and the relationship between the structural parameters and the equivalent force and the contact pressure as the optimization function, and the range of geometrical parameters as the boundary conditions. The optimization results show that when R=54 mm, H1=5.5 mm, H2=3 mm, and H3=2.5 mm, the equivalent force under the temperature and casing deformation conditions are reduced by 8.7% and 1.6%, respectively, and the contact pressure is increased by 10.4% and 3.4%. Especially in the high temperature working condition (201.8 ℃), the risk of specimen fracture is avoided, and the structural safety and sealing are effectively improved.In the experimental verification section, an ultra-high pressure simulation system was set up to test the optimized dissolvable ball seats at 70 MPa. A 5½-inch standard casing (inner diameter 124.26 mm) and high-precision pressure monitoring equipment were used to carry out the 70 MPa holding pressure test. The results show that the pressure fluctuation rate of the optimized sealing ring is less than 0.5% during the holding pressure period, the mass of the bucket before and after weighing remains constant at 2.689 kg, and the disassembly observation shows that there is no liquid residue in the inner wall of the casing, and the metal sealing ring has no plastic deformation or fracture. It shows that it is suitable for segmental fracturing operations in deep shale gas reservoirs and casing deformation well sections.In summary, this study proposes a collaborative optimization strategy of groove geometric parameters, breaks through the limitations of traditional empirical design, and establishes a four-dimensional parameter matching model of "radius-width-groove width and depth"; through the research method of "theoretical analysis-simulation optimization-experimental validation", this study reveals the mechanism of the multifactorial interactions of the metal sealing ring, and quantifies the contribution weights of the parameters to the sealing performance. Through the research method of "theoretical analysis - simulation optimization - experimental validation", the mechanism of multi-factor interaction of metal sealing ring is revealed, the contribution of each parameter to the sealing performance is quantified, and the key parameters of the dissolvable ball seat metal sealing ring are optimized by the response surface method, which significantly improves the safety and sealing performance of the metal sealing ring, especially in the adverse working conditions of high temperature and high pressure. Finally, the optimized structure achieves zero leakage in the 70 MPa high-pressure experiment, and the error between simulation and experiment is less than 5%, which verifies the reliability of the method. It provides theoretical support and engineering examples for the design of metal sealing rings under complex working conditions, which is of great value to promote the efficient development of unconventional oil and gas resources.